Change process in brief cognitive behaviour therapy workshop for psychological distress and mental health literacy among primary care self-referrals - Sam, Jeng Mun (2021)
The prevalence of psychological distress in primary care appears to be high, yet majority of the individuals who can benefit from early and evidenced-based psychological approach are limited. Barriers concerning stigma, lack of access to psychological interventions, high volume of primary care attendees, and poor mental health literacy are among the factors that contribute to the access of adequate treatments. The study examined psychological distress and mental health literacy (MHL) among primary care attendees in the suburban community. There were two interlinked phases in the study. In phase 1 (detection phase), the sociodemographic factors (age, gender, ethnicity, and education level) were discussed as predictive variables to psychological distress and MHL to inform on the intervention phase in phase 2. The prevalence of psychological distress using cross-sectional study design among the suburban primary care community were an important determinant for the justification for phase 2 using the DASS-21 questionnaire. The first phase found a prevalence of 16.7% for at least mild level of depressive symptoms, 15% for at least mild level of anxiety symptoms, and 4.8% for at least mild level of stress symptoms among 293 primary care attendees using systematic random sampling. Gender as one of the sociodemographic factors was found to be the only predictor for psychological distress and mental health literacy using multiple linear regression. These findings from phase 1 highlighted the importance to integrate a feasible and evidenced-based psychological intervention in the primary care level, therefore phase 2 (intervention phase) studies the implementation of change process using the brief Cognitive Behavioral Therapy (b-CBT) as a potential approach in managing psychological distress and improving MHL among 73 primary care self referrals using purposive sampling. One-way repeated measure multivariate analysis of variance (MANOVA) was used to analyze the nonrandomized quasi-experimental study for the change process in psychological distress and MHL. Results revealed that there were significant differences in three time-points (pre-, post-, and one-month follow-up) for psychological distress and MHL using DASS-21 and Mental Health Knowledge Schedule (MAKS). The implementation strategy of b-CBT showed positive changes in integrating brief, nonstigmatized, and evidenced-based psychological approach to the primary care level. Potential feasibility on the implementation of b-CBT workshop to improve psychological distress and MHL can be found in the study. However, the self-referral characteristics of the attendees remained unknown. The reporting of this thesis follows TREND statement reporting guidelines.